SEMIOTIC SIGNS OF FEMALE GHOST REPRESENTATION IN “MAMA” MOVIE - Anugrah, Nur Fitri; Halim, Abd; Nurfadhilah, Auliyanti Sahril (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
Semiotics, as the study of signs and meaning, plays an important role in understanding various forms of communication, including movies. The relationship between movies and semiotics is very close because semiotics is the study of signs and meanings. This research aims to find out the types of semiotic signs and meanings that indicate “mama” as a frightening and complex supernatural entity. This research uses a descriptive qualitative approach. Primary data sources in this research are obtained by watching the movie that is the object of research. I will use the film “mama” as data, and the script of the film to analyze. And secondary data is obtained from journals, articles, books, and internet sites that support this research. Through the application of Peirce's triadic triangle theory, this research seeks to understand more about the sign system used in the movie 'Mama'. Based on the results of the analysis, I found 27 semiotic signs divided into 3 types, namely icons, indexes, and symbols. The three categories contribute to building the horror image and character depth. Overall, the semiotic approach provides a richer insight into how movies convey messages and emotions to the audience.